Students' Perception of Writing Division of UKBA to Organize Idea in Writing - Putri, Dena Rahmadani; Arianto, M. Affandi (Journal of English Language Teaching, 2024)
Writing has always been included in most difficult English language courses as one of the four language skills. Although writing skills especially in organizing idea is hard to master, but there are ways to support writing skills. One of them is joining a writing community. This research discovered non-English major students’ perception of the writing division of UKBA to organize idea in writing This research was quantitative design with the data collection technique using an online close-ended questionnaire. The respondents in this study were 30 non-English members of the writing division of UKBA. They were given 7 close-ended questions. The result showed that non-English major students have a positive perception with values integration showing 77,50% in the criteria ‘very high percentage’. Thus, the Writing division can be established by other universities to improve students’ writing skills. In addition, further research related to non-English members' perception toward other components of writing is suggested to do